Analysis of Human Resource Needs in Inpatient Medical Record Officers Using WISN and ABK-Kes Methods in “X” Hospital - Avinda, Nadya Auliya; Giovany, Merlinna Resti; Amalia, Nuke; Rustam, Muh Zul Azhri; Salsabilla, Elma; Pertiwi, Shafira Zahra Ratu (Universitas Muhammadiyah Sidoarjo, 2024)
Every hospital must have qualified human resources both in the field of medical and health personnel. Hospitals have a responsibility to fulfill health service criteria. One of the minimum services that must exist in hospitals is medical records. Several hospitals in Indonesia, there are problems related to the needs of Human Resources (HR) in the medical records, including problems regarding the completeness of filling out medical records and high workloads. Therefore, it is necessary to calculate the staffing needs of the medical records and health information unit using the Workload Indicator Staffing Needs (WISN) method and Health Workload Analysis (ABK-Kes) in the inpatient unit at Hospital